Pre-season planing strategies of Italian Serie A clubs during 2009/10 - 2011/12 soccer seasons - Francioni, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
In soccer, pre-season period is a fundamental phase of the entire annual periodization however there is a lack of information about how clubs plan it (Cadwell & Peters, 2009). Thus, the aim of present study was to analyze the preseason planning of Italian Serie A (First League) clubs during three consecutive soccer seasons (2009/10; 2010/11; 2011/12). Methods: For each season investigated clubs were divided in three groups, according to the official ranking of the previous season: 1) 1-6 ranked (R1-6); 2) 7-17 ranked (R7-17); 3) the 3 clubs up-graded from Serie B (SB). Furthermore, clubs were divided in two geographical groups (i.e., northern and southern). A descriptive analysis was applied to investigate the following parameters: OS, duration of the off-season period (i.e., from the last official match of previous season to the first pre-season training); PP, overall duration of pre-season period (i.e., from the first training to the first official match); TC, number of days of the pre-season period spent in training camp; TP, duration of transition phase (i.e., from the last official match of previous season to the first one; FM, number of friendly matches played during the pre-season period. Results: In relation to the clubs` rank of the three seasons data showed a lower SD for TC and PP, which had a mean of 20±2 days (range: 18-21 days), 39±2 days (range: 38-41 days), respectively, Conversely, a higher SD was registered for TP and OS, which had a mean of 84±7 days (range: 77- 91 days), 45±6 days (range: 39-50 days), respectively. Furthermore FM showed a mean of 6 marches. The same trend of data was showed also according to the geographical groups analysis. Discussion: These findings suggest that, independently by clubs` rank and geographical groups, clubs adopted very similar pre-season planning strategies for TC, PP and FM. This aspect can be explained by the training strategies (i.e. necessity and choices of coaches) and the economical support that each clubs receive (i.e. sponsors, paid camps, etc.). Conversely, the TP and OS gaps can be explained by the prestige (i.e. level of national and international competition) of clubs and the calendar constriction.